Patient-identified priorities for a mental health program tailored to premenstrual dysphoric disorder - Sneha Chenji; Christine Bueno; May Ly; Sandi MacDonald; Rebekka Chartier; Catherine Lunn; Jennifer L. Gordon (Women's Health)
Background: There are no mental health programs tailored to premenstrual dysphoric disorder (PMDD). Objectives: Examine the content and features that PMDD patients desire in a mental health program. Design: Anonymous online survey. Methods: A survey, co-developed with PMDD patients, was distributed to followers of the International Association for Premenstrual Disorders (IAPMD) on social media. Respondents rated the importance of addressing various PMDD symptoms, psychosocial consequences, psychoeducational topics, and their preference for various techniques and features. Results: In total, 308 respondents rated suicidality, feelings of hopelessness and anxiety, and impacts on one’s relationship with one’s partner and children as important content areas for a PMDD-tailored mental health program. Providing evidence-based information and teaching techniques for managing distressing thoughts and emotions were also highly desired. Conclusion: Our findings help inform the development of a new mental health program that specifically addresses the unique emotional and psychosocial challenges associated with PMDD.